Combining the uniform design-based ray procedure with combination index to investigate synergistic lethal toxicities of ternary mixtures on Caenorhabditis elegans. Issue 22 (20th May 2016) - Tang, Han-Xiao; Liu, Shu-Shen; Li, Kai; Feng, Li
Abstract : A method combining the uniform design-based ray procedure and combination index integrated with observation-based confidence intervals is proposed to assess the combined toxicities of ternary mixtures on C. elegans . Abstract : A method combining the uniform design-based ray procedure (UD-Ray) and combination index (CI) integrated with observation-based confidence intervals (OCIs) was proposed to assess the combined toxicities of ternary mixtures of Cu, ionic liquids (1-hexyl-3-methylimidazolium bromide ([hmim]Br) or 3-methyl-1-octylimidazolium chloride ([omim]Cl)) and pesticides (dichlorvos (DIC) or glyphosate (GLY)) to Caenorhabditis elegans ( C. elegans ). A 96-well microplate was selected as an exposure experiment carrier where six blanks and 12 concentration treatments of a chemical or a mixture ray in four replicates were set. Lethality to C. elegans after 24 h of exposure to the chemical was taken as the toxicity endpoint. A data normalization method was introduced to calibrate the number of worms in various wells. UD-Ray was used to design the basic concentration compositions of five mixture rays (R1–R5) with different mixture ratios, because the UD-Ray can effectively simulate various concentration compositions in the mixture concentration space. Combination index (CI) independent of the action modes of the components was used to evaluate the combined toxicities of various mixtures. It was shown that 11 out of 20 mixture rays in four ternary mixture systems (Cu–DIC–[hmim]Br, Cu–DIC–[omim]Cl, Cu–GLY–[hmim]Br and Cu–GLY–[omim]Cl) display obvious synergistic interactions. The interactions of another nine rays changed from antagonism through additive action to synergism with increasing concentration. Moreover, one mixture ray was designed by fixed no observed effect concentration (NOEC) ratio to validate the predictability of the UD-Ray mixtures. The similarity of interactions in the mixture rays designed by the UD-Ray and fixed NOEC ratio demonstrated that the UD-Ray mixtures can simulate or predict the fixed NOEC ratio mixtures.